Experimental and Theoretical Characterization of the Magnetic Properties of CuF2(H2O)(2)(pyz) (pyz = pyrazine): A Two-Dimensional Quantum Magnet Arising from Supersuperexchange Interactions through Hydrogen Bonded Paths - Manson, J; Conner, M; Schlueter, J; McConnell, A; Southerland, H; Malfant, I; Lancaster, T; Blundell, S; Brooks, M; Pratt, F; Singleton, J; McDonald, R; et al. (2008)
The structural, electronic, and magnetic properties of the new linear chain coordination polymer CuF 2(H 20) 2(pyz) (pyz = pyrazine) were determined by single crystal X-ray diffraction at various temperatures, SQUID magnetometry, pulsed-field magnetization, ESR, muon-spin relaxation (uSR), and electronic structure calculations. Each Cu 2+ ion of CuF 2(H 2O) 2(pyz) is located at a distorted CuF 2O 2N 2octahedron with axial elongation along the Cu-N bonds. These octahedra are tethered together by strong F. . . H-O hydrogen bonds to yield two-dimensional (2D) square nets in the bc-plane that are linked along the α-direction by pyrazine linkages. Measurements of the g-factor by ESR along with first principles density functional theory electronic structure calculations show that the magnetic orbital of the Cu 2+ ion lies in the CUF 2O 2 plane thus forming a 2D antiferromagnetic square lattice. A broad maximum observed in χ(T) at 10 K indicates a modest spin exchange interaction through the Cu-F. . . H-O-Cu supersuperexchange paths, and a theoretical fit of χ(T) to a 2D square model gives J 2D LK B= -5.58(1) K (in the convention where J rather than 2J is used for spin exchange). At lower temperatures, χ(T) shows a sharp peak at ̃2.6 K, which signals a transition to a long-range magnetic ordering as confirmed by coherent precession of implanted muons. Isothermal M{B) measurements made at 0.5 K on an aligned single crystal reveal magnetic saturation, M sat, at 28.8 T (Blla) while a higher field of 33.1 T is required to saturate the spins when B is applied perpendicular to the α-axis thus showing clear anisotropy in these orientations. The presence of strong hydrogen bonds in CuF 2(H 20)2(ρyz) causes the chains to adopt a tilted packing arrangement, thus leading to a novel ground-state likely characterized by spin-canting within the 2D layers and a markedly increased critical temperature relative to the well-known Cu(NO 3) 2(pyz) polymer chain compound. © 2008 American Chemical Society.